Transcriptomics of Environmental Enrichment Reveals a Role for Retinoic Acid Signaling in Addiction - Zhang, Yafang; Kong, Fanping; Crofton, Elizabeth J.; Dragosljvich, Steven N.; Sinha, Mala; Li, Dingge; Fan, Xiuzhen; Koshy, Shyny; Hommel, Jonathan D.; Spratt, Heidi M.; Luxon, Bruce A.; Green, Thomas A. (Frontiers in Molecular Neuroscience, 2016)
There exists much variability in susceptibility/resilience to addiction in humans. The environmental enrichment paradigm is a rat model of resilience to addiction-like behavior, and understanding the molecular mechanisms underlying this protective phenotype may lead to novel targets for pharmacotherapeutics to treat cocaine addiction. We investigated the differential regulation of transcript levels using RNA sequencing of the rat nucleus accumbens after environmental enrichment/isolation and cocaine/saline self-administration. Ingenuity Pathways Analysis (IPA) and Gene Set Enrichment Analysis (GSEA) of 14,309 transcripts demonstrated that many biofunctions and pathways were differentially regulated. New functional pathways were also identified for cocaine modulation (e.g., Rho GTPase signaling) and environmental enrichment (e.g., signaling of EIF2, mTOR, ephrin). However, one novel pathway stood out above the others, the retinoic acid (RA) signaling pathway. The RA signaling pathway was identified as one likely mediator of the protective enrichment addiction phenotype, an interesting result given that nine retinoic acid signaling-related genes are expressed selectively and at high levels in the nucleus accumbens shell (NAcSh). Subsequent knockdown of Cyp26b1 (an RA degradation enzyme) in the NAcSh of rats confirmed this role by increasing cocaine self-administration as well as cocaine seeking. These results provide a comprehensive account of enrichment effects on the transcriptome and identify retinoic acid signaling as a contributing factor for cocaine addiction.